Multispectral Optoacoustic Tomography: Intra- and Interobserver Variability Using a Clinical Hybrid Approach - Helfen, Anne (J Clin Med, 2019)
Multispectral optoacoustic tomography (MSOT) represents a new imaging approach revealing functional tissue information without extrinsic contrast agents. Using a clinical combined ultrasound (US)/MSOT device, we investigated the interindividual robustness and impact of intra- and interobserver variability of MSOT values in soft tissue (muscle and subcutaneous fat) of healthy volunteers. Semiquantitative MSOT values for deoxygenated (Hb), oxygenated (HbO(2)) and total hemoglobin (HbT), as well as oxygen saturation (sO(2)), were calculated for both forearms in transversal and longitudinal probe orientation (n = 3, 8 measurements per subject). For intraobserver reproducibility, the same examiner investigated three subjects twice. Mean values of left vs. right forearm and transversal vs. longitudinal probe orientation were compared using an unpaired Student’s t test. Bland Altmann plots with 95% limits of agreement for absolute averages and differences were calculated. Intraclass correlation coefficients (ICC 2,k) were computed for three different examiners. We obtained reproducible and consistent MSOT values with small-to-moderate deviation for muscle and subcutaneous fat tissue. Probe orientation and body side had no impact on calculated MSOT values (p > 0.05 each). Intraobserver reproducibility revealed equable mean values with small-to-moderate deviation. For muscular tissue, good ICC was obtained for sO(2). Measurements of subcutaneous tissue revealed good-to-excellent ICCs for all calculated values. Thus, in this preliminary study on healthy individuals, clinical MSOT provided consistent and reproducible functional soft tissue characterization, independent on the investigating personnel.